2015
DOI: 10.5194/bg-12-945-2015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of meteorology and anthropogenic pollution on chemical flux divergence of the NO–NO<sub>2</sub>–O<sub>3</sub> triad above and within a natural grassland canopy

Abstract: Abstract. The detailed understanding of surface-atmosphere exchange fluxes of reactive trace gases is a crucial precondition for reliable modelling of processes in atmospheric chemistry. Plant canopies significantly impact the atmospheric budget of trace gases. In the past, many studies focused on taller forest canopies or crops, where the bulk plant material is concentrated in the uppermost canopy layer. However, within grasslands, a land-cover class that globally covers vast terrestrial areas, the canopy str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…The contribution of NO-NO 2 -O 3 chemistry to observed ozone fluxes can be estimated with ozone, NO, and NO 2 fluxes at two heights (Finco et al, 2018;Fitzjarrald & Lenschow, 1983;Lenschow & Delany, 1987;Vilá-Guerau de Arellano et al, 1993). An empirical technique only requiring flux measurements at one height has also been used (e.g., Plake, Sörgel, et al, 2015;Stella et al, 2012;Vuolo et al, 2017). This empirical technique assumes flux divergences of NO, NO 2 , and ozone are logarithmic with height, but the theoretical basis for this assumption is lacking.…”
Section: Fast Ambient Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of NO-NO 2 -O 3 chemistry to observed ozone fluxes can be estimated with ozone, NO, and NO 2 fluxes at two heights (Finco et al, 2018;Fitzjarrald & Lenschow, 1983;Lenschow & Delany, 1987;Vilá-Guerau de Arellano et al, 1993). An empirical technique only requiring flux measurements at one height has also been used (e.g., Plake, Sörgel, et al, 2015;Stella et al, 2012;Vuolo et al, 2017). This empirical technique assumes flux divergences of NO, NO 2 , and ozone are logarithmic with height, but the theoretical basis for this assumption is lacking.…”
Section: Fast Ambient Chemistrymentioning
confidence: 99%
“…In a shaded forest canopy, photolysis of NO 2 (i.e., R2) is expected to be low. In general, the effects of R1 on ozone fluxes are usually small (Kramm et al, ; Plake, Sörgel, et al, ; Rannik et al, ; Stella et al, ; Vuolo et al, ) because there is typically much more ozone than NO x (=NO + NO 2 ). However, some studies suggest R1 accounts for a nonnegligible influence on observed ozone fluxes (Dorsey et al, ; Finco et al, ; Lamaud et al, ; Neirynck & Verstraeten, ; Rummel et al, ), especially at night when there is relatively high NO x .…”
Section: Theory Models and Observations Of Terrestrial Ozone Deposimentioning
confidence: 99%
“…Observed ozone fluxes measured near the canopy top are commonly interpreted as dry deposition only but may be influenced by fast chemical losses of ozone such as the NO + O 3 reaction (Finco et al., 2018; Kramm et al., 1995; Plake et al., 2015). Negative NO‐O 3 Is ${I}_{\mathrm{s}}$ means that the influence of NO on the ozone flux is even weaker than under the assumption of well‐mixed conditions.…”
Section: Comparison To Previous Work and Implications For Ozone Dry D...mentioning
confidence: 99%
“…NO x , and especially NO 2 , are toxic gases for humans, exposure to which increases risks of various respiratory diseases. The World Health Organization gives guidelines for NO 2 exposure limits, both annual means (40 µg m −3 ) and 1 h mean (200 µg m −3 ) (Prüss-Üstün et al, 2016). For O 3 , only a short-term threshold is given (100 µg m −3 for the 8 h mean) because there are fewer studies on long-term exposure.…”
Section: Introductionmentioning
confidence: 99%